Secure and high throughput routing protocol with QoS constraints in cognitive wireless Mesh networks - Zhu-fang KUANG; Zhi-gang CHEN; Guo-jun WANG; Hui LIU (Tongxin xuebao)
A routing metric SIEB which includes link security，link conflict，link reliability and link available bandwidth was proposed.The SIEB includes link security and link performance two aspects.In order to resist various hole attack，the link trust value based on two hop neighbor feedback is computed in link security weight computing of SIEB.On this basis，a link security weight computing algorithm LSWC and a link performance weight computing algorithm LSPC were proposed，and a distributed routing protocol SIEBP with QoS constraints in cognitive wireless Mesh network was proposed.Finding safety routing path and maximizing the network throughput are the objective of SIEBP.Simulation results show that SIEBP routing protocol can achieve expectation goal.It can not only find safety routing path which can resist black hole attack，gray hole attack and worm hole attack，but also obtain a higher network throughput.